Implementasi Pendidikan Karakter Dalam Pembelajaran IPA di MIN Pemangkat Kabupaten Sambas Kalimantan Barat - Purniadi Putra (JIP Jurnal Ilmiah PGMI, 2017)
This study aims to know and examine more deeply about the implementation of character education in science learning in MIN Pemangkat Sambas regency, knowing and deepening about the character values implanted in science learning in MIN Pemangkat Sambas regency. This research is qualitative descriptive research. The location of research is in Madrasah Ibtidaiyah Negeri Pemangkat Sambas Regency using primary data source and sekuder is the technique of analyzing data used interview and documentation, data analysis is qualitative analysis. The results of this study indicate that implementation of character education in science learning in MIN Pemangkat Sambas Regency implemented in three stages of planning, implementation, evaluation and follow up. Priority character values are character values that must be instilled by educators in science learning activities. Character values in the priorities embedded include honest values, discipline, hard work and responsibility.